INFLUENCE OF MICROBIOLOGICAL PREPARATIONS AND MICROFERRALS ON SOYBEAN PRODUCTIVITY IN CONDITIONS OF AGROCLIMATIC RISKS - Ласло, Оксана; Олепір, Роман (SWorldJournal, 2025)
Soybean is an important legume crop that solves the problem of vegetable protein and fat deficiency, improves the nitrogen balance of the soil. A rationally constructed fertilization system allows for high and full-fledged soybean seed yields, taking int